Conflict risk and defense expenses and their impact on the economic growth - Dinçer, Hasan; Hacıoğlu, Ümit; Yüksel, Serhat (IGI Global, 2021)
The main purpose of this chapter is to identify the effects of conflict risk and defense expenses on economic growth. Within this scope, annual data of 17 emerging economies for the period between 1989 and 2014 were analyzed. In addition to this situation, Dumitrescu Hurlin panel causality test was taken into consideration in order to reach the objective. As a result of the analysis, it was determined that there is a causality relationship between conflict and defense expenses for these countries. This situation shows that emerging countries, which have high conflict risk, also increase defense expenses so as to minimize the negative effects of these conflicts. Additionally, it was also identified that economic growth is a significant reason of high defense expenses. In other words, it can be said that when the economy of an emerging country is developed, it gives more importance to defense expenses in order to take action for this conflict.
Keywords: Economic Growth; Defense Expenses; Conflict Risk